Economic Consequences of the COVID-19 Outbreak: the Need for Epidemic Preparedness - Pak, Anton; Adegboye, Oyelola A.; Adekunle, Adeshina I.; Rahman, Kazi M.; McBryde, Emma S.; Eisen, Damon P. (Frontiers in Public Health, 2020)
COVID-19 is not only a global pandemic and public health crisis but it has also severely affected the global economy and financial markets. Significant reductions in income, rise of unemployment and disruptions in transportation, service and manufacturing industries are among the consequences of disease mitigation measures implemented in many countries. It has become clear that most governments in the world have underestimated the risks of rapid COVID-19 spread and were mostly reactive in their crisis response. As disease outbreaks are not likely to disappear in the near future, proactive international actions are required to not only save lives but also protect economic prosperity.